A virtual reality simulation of a novel way to illuminate the surgical field – A feasibility study on the use of automated lighting systems in the operating theatre - Cetin, Timur; Mühlenbrock, Andre; Zachmann, Gabriel; Weber, Verena; Weyhe, Dirk; Uslar, Verena (Frontiers in Surgery, 2023)
Surgical lighting systems have to be re-adjusted manually during surgery by the medical personnel. While some authors suggest that interaction with a surgical lighting system in the operating room might be a distractor, others support the idea that manual interaction with the surgical lighting system is a hygiene problem as pathogens might be present on the handle. In any case, it seems desirable to develop a novel approach to surgical lighting that minimizes the need for manual interaction during a surgical procedure. We investigated the effect of manual interaction with a classical surgical lighting system and simulated a proposed novel design of a surgical lighting system in a virtual reality environment with respect to performance accuracy as well as cognitive load (measured by electroencephalographical recordings). We found that manual interaction with the surgical lights has no effect on the quality of performance, yet for the price of a higher mental effort, possibly leading to faster fatigue of the medical personnel in the long run. This effect can be avoided with the novel surgical lighting system, which negates the need for manual interaction and leads to a performance quality comparable to the classical lighting system, yet with less mental load for the surgical personnel.